Noise in Indonesian urban areas: rules and facts - Mediastika, Christina E.; Sudarsono, Anugrah S.; Utami, Sentagi S.; Fitri, Isnen; Drastiani, Rizka; Winandari, M. I. Ririk; Rahman, Akbar; Kusno, Asniawaty; Mustika, N. W. Meidayanti; Mberu, Yuliana B.; Yanti, Ressy J.; Rachman, Zulfi A. (Journal of Architecture and Urbanism, 2022)
Irresponsible noise management by the concerned authorities and society’s indifference has made noise in Indonesian urban areas a nightmare. The current noise regulation in Indonesia, which define 55 dB(A) as the lowest permissible noise level generated in residential areas, is outdated. This study investigates how urban communities reacted to the implementation of this outdated regulation. Data was collected by searching online open sources for noise-related keywords used in public complaints, court cases, authority campaigns, etc. The collected data was then plotted in an Excel sheet to create a modest statistical trend, and the detailed information on how the government and court ruled the case was treated as a transcript to be analysed qualitatively. The study results are to be compared and discussed with noise facts of those in more advanced countries. The discussion shows that the noise case in Indonesia is significantly minor compared to other countries with similar populations. Noisemakers were reported to have won in 44% of noise complaints that went to court. This may be the reason for the Indonesians’ apathy toward the settlement of noise-related complaints by the city government and the fairness of tribunal processes.